2014
DOI: 10.1007/s00167-014-2863-2
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin–aggrecan complex as a marker for cartilage degradation in non-arthritic hips

Abstract: Purpose To report hip synovial fluid cytokine concentrations in hips with and without radiographic arthritis. Methods Patients with no arthritis (Tonnis grade 0) and patients with Tonnis grade 2 or greater hip osteoarthritis (OA) were identified from patients undergoing either hip arthroscopy or arthroplasty. Synovial fluid was collected at the time of portal establishment for those undergoing hip arthroscopy and prior to arthrotomy for the arthroplasty group. Analytes included fibronectin-aggrecan complex (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Synovial fluid access at the time of surgery is more feasible but often requires a lavage, which limits the accuracy of biomarker concentration measurements [2]. Significant heterogeneity exists across different studies that can be difficult to adequately account for in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Synovial fluid access at the time of surgery is more feasible but often requires a lavage, which limits the accuracy of biomarker concentration measurements [2]. Significant heterogeneity exists across different studies that can be difficult to adequately account for in a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular biomarker profiles for these conditions are likely different and may account for heterogeneity in the current literature on biomarkers in hip OA that may contribute to the lack of identification of a clinically useful biomarker. The literature on biomarkers in prearthritic hip disease is limited with three studies investigating three different biomarkers [2,4,16] including two studies on FAI, one on pain of unspecified etiology and no studies investigated hip dysplasia. Bedi et al [4] performed the best study to date in a small population with FAI and demonstrated differences in serum COMP and CRP compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work identified a biomarker (FAC), which was shown to be elevated in patients undergoing hip arthroscopy for FAI when compared to those undergoing arthroplasty for OA. Additionally, it was found that those patients undergoing arthroscopy who were noted to have cartilage loss requiring microfracture at the time of operative intervention had elevated levels of FAC compared to those with less cartilage loss who did not meet the indication for microfracture [44]. This previous study did not find a relationship between biomarker concentration and pre-operative assessment scores; however, it did not study the relationship between cytokine concentration and change in outcome scores.…”
Section: Discussionmentioning
confidence: 99%